Proteasome modulator 9 gene Rs14259 polymorphism in patients with diabetic polyneuropathy - (:unkn) unknown (Turkish Neuropsychiatric Society, 2021)
Introduction: Diabetic polyneuropathy (DPN) is a major chronic neurological complication of diabetes mellitus (DM) and typically presents as diabetic sensory polyneuropathy (DSPN). Whereas some patients with similar risk factors develop polyneuropathy, others don’t, which suggests that genetics plays an important role in the progression of disease. The proteasome modulator 9 gene (PSMD9) is a transcriptional regulator of the insulin gene and its variants cause beta-cell dysfunction that devastates insulin transcription. The aim of this study was to determine the correlation between PSMD9 rs14259 polymorphism and the risk of DSPN in Turkish DM patients with DPN. Methods: The study included 31 DM patients with DSPN and 29 healthy controls. All participants underwent electrophysiological investigation. In addition, DNA was isolated from peripheral blood samples for the genotyping of PSMD9 rs14259 polymorphism. Results: Mean age in the DSPN and control groups was 58.03±9.59 years and 57.62±12.32 years, respectively. There were significant differences between the DSPN and controls groups in the frequencies of the genotype for AA (n=9 and n=12, respectively), AG (n=10 and n=15, respectively), and GG (n=12 and n=2, respectively). According to the distribution of PSMD9 rs14259 polymorphism, 45.2% (n=28) of the patients and 67.2% (n=39) of the controls had the A allele, and 54.8% (n=34) of the patients and 32.8% (n=19) of the controls had the G allele, whereas the frequency of the G allele of rs14259 was significantly higher in the DSPN group (X2=1.059, P=0.015) than in the control group (OR: 2.49; 95% CI: 1.18–5.23). Conclusion: The present findings show that the GG genotype and G allele of PSMD9 rs14259 polymorphism may be associated with an increased risk of DSPN in Turkish DM patients. © 2019 by Turkish Association of Neuropsychiatry.
Keywords: Diabetes mellitus; Diabetic polyneuropathy; PSMD9; Rs14259